Digital forensics threatscape and best practices - Sammons, John (Syngress is an imprint of Elsevier, 2015)
Information security practitioners are faced with a never-ending stream of threats and attacks, and need to be aware of how these threats and attacks are continually evolving. One of the primary challenges is keeping up with the sheer volume of information around these threats and making sense of the patterns as they evolve. Information Security and Digital Forensics: Threatscape and Best Practices provides you with incisive analysis from a panel of expert authors, led by John Sammons, bestselling author of The Basics of Digital Forensics. This complete reference surveys the landscape of information security threats and provides a coherent overview of the threatscape in a broad range of topics, providing practitioners and researchers alike with a comprehensive and coherent overview of the threat landscape and what can be done to manage and prepare for it, including insights in each of five core topics: Digital Forensics, Information Assurance/Security, CyberCrime, Open Source Intelligence, and Electronic Discovery